Volleyball injury epidemiology - Reeser, J. C. (2000)
Volleyball is perhaps the world's most popular participation sport. It is played both indoors and outdoors by both young and old, able bodied and disabled, elite and recreational, and male and female athletes. Several studies have been published examining injury patterns among volleyball players. Due to differences in study design, the injury rates reported by these studies vary substantially. It is nevertheless clear that volleyball athletes are in general at greatest risk for non-surgical injuries to ligaments, tendons, and muscles which occur acutely as a result of dynamic overload (eg. sprains and strains), or as a consequence of chronic overuse (eg. tendinopathies). Spiking and blocking appear to be "high risk" activities. The most frequently injured body parts are the ankle, knee, shoulder, and low back. Perhaps the best data are available from the National Collegiate Athletic Association's Injury Surveillance System (Indianapolis, Indiana, USA). These data suggest that female volleyball athletes experience fewer time-loss injuries than do female athletes participating in other collegiate sports. Given the recent popularity of two-person beach volleyball, there are surprisingly few studies comparing the injury patterns characteristic of indoor and beach volleyball. Paralympic volleyball has also been inadequately examined. An understanding of the extrinsic and intrinsic factors associated with volleyball related injuries, and of the injury patterns unique to the different varieties of volleyball enjoyed world-wide, is essential to providing the volleyball athlete with appropriate injury prevention strategies and optimum rehabilitation programs. (2000 Pre-Olympic Congress, Sports Medicine and Physical Education, International Congress on Sport Science, 7-13 September - Brisbane, Australia 2000)